LASIK 에 의한 난시의 교정 효과 - 김상준; Sang Jun Kim; 이주용; Joo Yong Lee; 차흥원; Hung Won Tchah (Daihan angwa haghoi jabji, 2001)
목적 :LASIK에 의한 복합 근시성 난시에서의 교정효과를 알아보고자 하였다. 대상과 방법 :1996년 1월 이후 본원에서 LASIK을 시행 받고 1년 이상 추적 관찰이 가능했던 환자들 중 술 전 난시량이 0.50D를 초과했던 83명 108안을 대상으로 수술 결과를 후향적으로 분석하였다. 결과 :평균나이는 28.9세(21~42세)이고,남자는 25명,여자는 58명이었다.술 전 난시량에 따라 I군(31안:0.50~0.75D),II군 (46안:1.00 D~1.75 D),III군(15안:2.00 D~2.75 D),IV군(16안:3.00 D~6.50 D)으로 분류했고 수술 1년 후 난시량은 각각 0.60 ±0.73 D,0.58 ±0.72 D,0.75 ±0.89 D,0.62 ±0.60 D로 각 군별로 유의한 차이가 없었다.벡터분석에서 난시축 교정이 30도 이상 벗어난 경우는 17.2%이었고,교정하고자 하는 난시 굴절력에서 0.50 D 이내로 교정된 경우는 수술 1년 후 각 군당 64.5,63,56,66.7%이었다.1년 후 나안시력 0.5 이상이 69%,0.8 이상이 46%이었다.교정시력은 수술 전과 비교시 대부분 변화가 없었다. 결론 : 복합 근시성 난시에서 수술 전 난시의 양에 상관없이 교정효과가 우수하여 수술 후 난시량은 모든 군에서 비슷하였다.〈한안지 42(7):967-971, 2001〉 Purpose : The authors studied the results of excimer laser in situ keratomileusis for correction of myopicastigmatism. Methods : The authors studied the results of 108 eyes(83 patients) who underwent excimer laser in situ keratomileusis for correction of myopic astigmatism and had preoperative atigmatism greater than 0.5 diopter(D). Each patient had been followed up for over 12 months since January 1996. Refractive errors, uncorrected visual acuity(UVA) and best corrected visual acuity(BCVA) were measured at postoperative 1, 3, 6 months and 1 year, respectively. And astigmatic changes were analyzed by vector analysis using the Holladay formula. Results : Twenty-five patients were male; 58 were female. Mean spherical equivalent was -11.64 D ±4.03 D preoperatively and -1.32 D±1.73 D at postoperative 1 year. In group I(31 eyes:0.50 D~0.75 D),II(46 eyes:1.00 D~1.75 D), III(15 eyes:2.00 D~2.75 D), IV(16 eyes:3.00 D~6.50 D), postoperative astigmatism were 0.60±0.73 D, 0.58±0.72 D, 0.75±0.89 D, 0.62±0.60 D at postoperative 1 year. In 17.2% of all the eyes, axis deviation within 30 degrees was noted 1 year after the surgery. By vector analysis, astigmatic errors were corrected within 0.50 D of the attempted amount in 64.5% of group I, 63.0% of group II, 56.0% of group III and 66.7% of group IV. UVA was 0.5 or better in 69%, and 0.8 or better in 46% at postoperative 1 year. Conclusions : BCVA did not change after the surgery in most of the eyes. The greater the amount of preoperative astigmatism, the more effective the postoperative astigmatic correction J Korean Ophthalmol Soc 42(7):967-971, 2001